Association of dietary fats with gut microbiota profile: How does palm oil fit in - Yap, Sia Yen; Voon, Phooi Tee; Cheah, Yoke Kqueen; Lee, Verna K.M.; Selvaduray, Kanga Rani (Malaysian Palm Oil Board, 2021)
Diet manipulation alters the gut microbiota composition. Gut dysbiosis is characterised by imbalanced bacteria composition that has been associated with high fat diet. Diets containing high animal fat induce pathogenic bacteria growth and similar bacterial profiles have been identified in obese adults and chronic disease patients. Conversely, diets containing high plant fat increase the abundance of beneficial bacteria. Habitual fat intakes modulate the bacterial species and their metabolites in different geographical locations and ethnicities. Dietary interventions using various degrees of fatty acid saturation reported reduced bacterial diversity in high saturated fatty acid (SFA) diet and increased in high monounsaturated fatty acid (MUFA) diet. However, high polyunsaturated fatty acid (PUFA) diet demonstrated a wide variation in bacterial diversity. These results suggested that the effects of dietary fats on gut microbiota composition are not fully established. Palm oil has almost balanced proportions of saturated and unsaturated fatty acids coupled with unique stereo-specificity fatty acids compositions and nutritional properties, making it the main vegetable oil in the Malaysian diet. However, its effect on the gut microbiota profile is still unknown. This review highlights the abundance of specific bacteria after consuming various dietary fats and proposes potential bacteria profile following the palm oil diet.